Prediction and Prioritization of Individual and Organizational Factors Affecting Turnover Intention based on Fuzzy Delphi and Analytical Hierarchy Process (AHP) Method: A Case Study of Employees of a Health Center in Ahvaz City in Iran - Davoud Afshari; Gholam Abbas Shirali; Zohre Shabgard (Muhandisī-i bihdāsht-i ḥirfah/ī, 2024)
Background and Objective: The present study aimed to identify and prioritize the factors affecting the desire to leave the job of employees of a health center in Ahvaz City, Iran. Materials and Methods: A descriptive-analytical study was conducted in health centers in Ahvaz in 2023. The factors influencing the desire to leave a job were identified through a literature review and the fuzzy Delphi method. Additionally, 100 employees completed Kim's Turnover Tendency Scale. In the final step, the identified factors were weighted and prioritized using the Analytical Hierarchy Process (AHP). Results: A total of 32 effective factors influencing the desire to leave work were identified and categorized into four groups: individual factors, organizational factors, job factors, and job-related factors. The findings from the AHP method indicated that age (0.213), education level (0.176), and work experience (0.143) from the category of individual factors, as well as salary, type of employment, and lack of promotion opportunities from the category of organizational factors, leadership and management style (0.243), changes in job descriptions (0.243), and organizational position (0.198), along with the employment of unqualified individuals (0.147) from the category of managerial factors, were identified as the most significant risk factors predicting the intention to leave a job among employees in health centers. Conclusion: By identifying and prioritizing the factors affecting the desire to leave the job among the employees of health centers, preventive measures can be defined and implemented to maintain the human resources providing health services.